(untitled) (Journal of Medicine, 2020)
SLE is one of the most common autoimmune disorders of women of childbearing age.It often manifests with various constitutional symptoms as well as combination of major organ involvement and outcome varies in different studies with current treatment. The present study is to see the patterns of organ involvement and outcomes at least after 6 months with standard treatment. This retrospective study was conducted in lupus clinic of two largest tertiary care hospitals in Dhaka city of Bangladesh over 2010 to 2019. It included 277 patients of SLE, diagnosed on the basis of ACR lupus diagnostic criteria and ACR lupus nephritis guideline and had received standard treatment. Outcomes were assessed by SLEDAI. The most common clinical manifestations were fever (71.8%), joint pain (71.4%), oral ulceration (54.8%), alopecia (36.4%), butterfly rash (28.5%), photosensitivity (32.1%) and Raynaud’s phenomenon (16.6%). Commonly involved major organ-systems were renal (41.5%), CNS (16.6%), pulmonary (7.2%), cardiac (3.2%) and hematological (12.2%). Renal biopsy was done in 91cases and the histology showed majority (37.3%) in class-IV. With standard treatment, a significant reduction of mean serum creatinine, proteinuria and SLEDAI was observed at least after 6 months. A total 35(12.63%) flares and 6 (2.17%) deaths occurred during the course of treatment. Renal and CNS are the most commonly involved major organ systems next to skin and joints. The overall outcome is favorable with standard treatment. J MEDICINE JUL 2020; 21 (2) : 89-92